2007
DOI: 10.1016/s0828-282x(07)70871-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrast echocardiography accurately predicts myocardial perfusion before angiography during acute myocardial infarction

Abstract: O ptimal therapy during acute myocardial infarction (AMI) includes prompt re-establishment of flow in the infarct-related artery (IRA) and effective reperfusion (1-3). Early, spontaneous reperfusion occurs in a small but significant proportion of IRAs (4,5), and the majority are reperfused with thrombolytic therapy. It is difficult to determine whether patency has been achieved at a given time in most patients without cardiac catheterization. The availability of a noninvasive method to rapidly assess myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For each parameter in each region, the mean value of three measurements was then calculated. Plots of contrast intensity versus time were constructed and fitted to an exponential function, y = A (1 − e − βt) [20]. The plateau of signal intensity (A) and the slope of maximum signal intensity rise (β) were measured, and the product of A × β was computed.…”
Section: Methodsmentioning
confidence: 99%
“…For each parameter in each region, the mean value of three measurements was then calculated. Plots of contrast intensity versus time were constructed and fitted to an exponential function, y = A (1 − e − βt) [20]. The plateau of signal intensity (A) and the slope of maximum signal intensity rise (β) were measured, and the product of A × β was computed.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of IRA's patency influences the decision-making process when planning for percutaneous intervention (PCI) as a life-saving procedure in acute myocardial infarction. 136 MCE showed superiority over thrombolysis in myocardial infarction (TIMI) score, providing accurate prognostic information regarding the risk of short- and long-term cardiac events. 137 Furthermore, intriguing preclinical conclusions that high-mechanical-index flashes during UEA infusion can restore defective microvasculature have motivated the clinical trial of MCE as a supportive therapeutic measure (so-called sonothrombolysis) in ST-elevated myocardial infarction.…”
Section: Contrast Echocardiographymentioning
confidence: 99%
“…Angiography is a gold standard technique to measure the patency of infarct-related artery (IRA) [ 6 ]. Non-invasive techniques such as an ECG can also be used to predict the reperfusion status [ 7 ]. Ahmed et al indicated in their pilot study that a 50% reduction in the sum of ST-segment elevations at four hours after intravenous streptokinase was a useful indicator of the outcome of reperfusion [ 8 ].…”
Section: Introductionmentioning
confidence: 99%